2023
DOI: 10.2147/ijn.s402410
|View full text |Cite
|
Sign up to set email alerts
|

Combined Ferromagnetic Nanoparticles for Effective Periodontal Biofilm Eradication in Rat Model

Abstract: Introduction The critical challenge for periodontitis therapy is thoroughly eliminating the dental plaque biofilm, particularly penetrating the deep periodontal tissue. Regular therapeutic strategies are insufficient to penetrate the plaque without disturbing the commensal microflora of the oral cavity. Here, we constructed a Fe 3 O 4 magnetic nanoparticle loading minocycline (FPM NPs) to penetrate the biofilm physically and effectively elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In fact, 14 out of 23 diagnostic studies were conducted using ultrasmall SPIONs. The hydrodynamic sizes of SPIONs and ultrasmall SPIONs were less than 100 nm in aqueous suspension, with the exception of two studies (Tong et al, 2023; Vu et al, 2021), where the authors reported sizes larger than 200 nm.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, 14 out of 23 diagnostic studies were conducted using ultrasmall SPIONs. The hydrodynamic sizes of SPIONs and ultrasmall SPIONs were less than 100 nm in aqueous suspension, with the exception of two studies (Tong et al, 2023; Vu et al, 2021), where the authors reported sizes larger than 200 nm.…”
Section: Resultsmentioning
confidence: 93%
“…The disease is characterized by a thick plaque buildup and the presence of resistant bacterial biofilm. Tong et al introduced dopamine‐coated SPIONs loaded with minocycline (an antibiotic drug) to combat periodontitis (Tong et al, 2023) (Table 3). These multifunctional nanoparticles displayed potent anti‐biofilm activity, biocompatibility, and magnetic targeting, allowing them to disrupt biofilm integrity and enhance drug penetration.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we have selected as an example some works of nanomedicines against biofilm infections using robust biofilm models and set ups: Tong et al used Fe 3 O 4 magnetic NPs as antibiofilm agents against periodontal bacterial biofilms and enhanced the penetration efficacy through magnetic targeting in an in vivo bacterial-induced periodontal inflammation model in rats (Tong et al, 2023). On the other hand, Fang et al employed cationic liposomes with enzymes (DNase I and Proteinase K) to disassemble Cutibacterium acnes biofilms in a cutaneous and catheter mouse model (Fang et al, 2021).…”
Section: Nanomedicines For Biofilm Treatment: Challenges and Limitationsmentioning
confidence: 99%